Tiered intervention: history and trends in Finland and the United States. Issue 1 (2nd January 2016) - Jahnukainen, Markku; Itkonen, Tiina
Abstract: This study explores the similarities and differences of relatively newly established tiered intervention models for the support of students with special needs in the United States (response to intervention) and in Finland (learning and schooling support). The current models in both countries consist of several tiers with fairly similar definitions. Despite the similarities, the history and political meaning of the tiered models are different in these countries. However, in both countries, part of the underlying political expectation is that the change to tiered intervention will promote inclusive education, but also diminish the number of special education students, and at the same time decrease the rising costs of special education funding. It is evident that there have been educational as well as political and financial objectives behind the restructuring in both countries. We conclude with a discussion on policy implications.